Optimal hydrothermal dispatch using Lagrangian decomposition and network flow programming - Dayco, Rolando Pascual
Optimal Hydrothermal Scheduling is a nonlinear optimization problem constrained by a large number of equality and inequality constraints. The original problems was therefore decomposed into a thermal subproblem and a hydro subproblem through the application of the principle of Lagrangian relaxation. The resulting thermal subproblem evolved into a set of economic dispatch problems, one for each time period, that can be optimized individually. An efficient linear search technique for solving economic dispatch problems was developed for this thesis. The hydro subsystem was modeled as a capacitated network flow model with linear and nonlinear arc costs. A unique three-piece linear approximation that explicitly represents the nonlinear hydro generation cost function enabled the use of a computationally efficient network flow programming technique. For systemwide studies, the algorithm iterates between the thermal and the hydro models until overall optimality is reached. It exhibited efficient and reliable convergence characteristics when tested on hydrothermal systems with different hydro-to-thermal generation capacity ratios.